Cross-sectoral coordination in the public sector: A challenge to leveraging agriculture for improving nutrition and health - Benson, Todd (International Food Policy Research Institute, 2011)
Healthy and active lives for all require adequate access to food, care, employment, health services, and a healthy environment. None of these determinants of good health and nutrition is sufficient by itself; all of them are necessary. The most efficient policy approach involves, accordingly, a coordinated effort across the various public sector ministries and agencies concerned. However, most governments and government agencies are organized in a way that makes coordination across sectors difficult to achieve